The Effect of Concrete Learning on Ibtidaiyah Madrasah Students' Reading and Writing Skills Improvement: Pengaruh Pembelajaran Konkrit Terhadap Peningkatan Keterampilan Membaca dan Menulis Siswa Madrasah Ibtidaiyah - Fitria, Siti Choirul; Nurdyansyah, Nurdyansyah (Indonesian Journal of Innovation Studies, 2022)
The problem raised in this study is whether there is an effect of concrete learning on improving reading and writing skills in class I MI Muhammadiyah 2 Kedungbanteng. This study aims to analyze how much influence concrete learning has on improving reading and writing skills in Indonesian subjects in class I MI Muhammadiyah 2 Kedungbanteng. To achieve this goal, the researchers used quantitative methods with pretest/posttest test tools and questionnaires. The sample of this study was class I MI Muhammadiyah 2 Kedungbanteng with a total of 24 students. There are several stages that researchers must go through in research, namely interviews with the homeroom teacher to get real problems, formulate hypotheses, collect data, analyze data and draw conclusions. In the sampling technique, the researcher used purposive sampling. Data analysis used a simple linear regression test with the help of SPSS 20 for windows. Based on the test results indicate that there is no effect of concrete learning on improving reading skills and there is an effect of concrete learning on improving writing skills. This can be proven by the results of the analysis of the effect of the significance value obtained from concrete learning with an increase in reading skills of 0.580 > 0.05, with t count -0.563 and t table 2.074 which results in H0 being accepted and Ha rejected, while concrete learning with improving writing skills obtained a significance of 0.677 <0.05 and t count writing -0.423 and t table 2.074 which resulted in Ho being rejected and Ha accepted.